Resveratrol-modified mesoporous silica nanoparticle for tumor-targeted therapy of gastric cancer. Issue 1 (1st January 2021) - Lin, Mingzhen; Yao, Wenxia; Xiao, Yao; Dong, Zhijie; Huang, Wei; Zhang, Fan; Zhou, Xinke; Liang, Min
ABSTRACT: Resveratrol (Res) has been shown to exhibit anti-cancer properties in gastric cancer. However, its clinical application is limited by its poor pharmacokinetics, stability, and low solubility. Hence, this study aimed to explore and verify a better delivery system for gastric cancer therapy. Using transmission electron microscopy, Fourier transform infrared (FTIR) spectroscopy, and ultraviolet (UV) spectrometry, we observed the shape and encapsulation of resveratrol-modified mesoporous silica nanoparticles (MSN-Res) that were synthesized by chemical methods. To explore the anti-cancer effects of these MSN-Res in vivo and in vitro, we established AGS and HGC-27 tumor-bearing mouse models. Meanwhile, the proliferation of gastric cancer cells in vitro and in vivo was assessed by Cell Counting Kit-8, EdU, and Ki-67 immunohistochemical staining methods, while cellular apoptosis, and invasion and migration were detected by TdT-mediated dUTP nick end labeling (TUNEL) and Transwell assays, respectively. FTIR and UV results showed that we successfully synthesized and loaded drugs. Safety evaluation experiments showed that neither MSN-SH nor MSN-Res had toxic effects on the normal tissues of animals. Moreover, in vitro experiments revealed that MSN-Res significantly inhibited the proliferation, invasion, and migration of gastric cancer cells. Furthermore, TUNEL assay showed that MSN-Res promoted apoptosis in gastric cancer. These results were confirmed by the nude mouse tumorigenesis experiment. In conclusion, we demonstrated that MSN-Res showed better inhibitory effect on the development of gastric cancer than Res alone, indicating that MSN-Res could be a promising drug delivery system for gastric cancer treatment.